Organizational Sustainability in the Era of Internal Auditing and Digital Accounting Information Systems - Irda Agustin Kustiwi (Cahaya Abadi Publisher, 2025)
This research aims to examine the role of internal audit and digital-based accounting information systems in supporting organizational sustainability. The research approach uses a qualitative method with a literature study design. The research population includes international scientific articles that discuss internal auditing, digital accounting information systems, and sustainability, with a sample of Scopus Q1, Q2, Q3, and Q4 indexed articles and journals as well as reputable international journals. The data collection technique was carried out through a search of the Scopus and Google Scholar databases with publication inclusion criteria for the 2020–2025 period. The data analysis method uses thematic analysis and narrative synthesis to identify the relationship patterns, strategic roles, and contribution mechanisms of internal audit and digital accounting information systems to sustainability. The results of the study show that internal audits play a role in strengthening governance, risk management, and sustainable internal control, while digital accounting information systems improve the transparency, accuracy, and timeliness of financial information. The integration of the two strengthens data-driven decision-making and supports the achievement of economic, social, and environmental sustainability. The implications of this research provide a conceptual contribution to the development of a sustainability framework based on internal audit and accounting digitization and become a practical reference for organizations in designing sustainability-oriented control and reporting systems.